DP1 receptor agonist, BW245C inhibits diet-induced obesity in ApoE−/− mice. Issue 2 (March 2018) - Kumar, Sunil; Palaia, Thomas; Hall, Christopher; Ragolia, Louis
Highlights: DP1 receptor agonist inhibits high fat diet-induced obesity in ApoE −/− mice. DP1 receptor agonist has cardiovascular benefits. DP1 receptor agonist significantly improved glucose tolerance and fasting glucose levels. DP2 receptor agonist impairs glucose tolerance. Bile acid level increases in response to DP1 receptor agonist. Summary: Background/objective: Lipocalin Prostaglandin D2 synthase (LPGDS) contributes to the production of PGD2, which has been associated with adipogenesis. In this study, we aimed to investigate the role of PGD2 on obesity through its DP1 and DP2 receptor signaling using intraperitoneal injection of their respective agonists and antagonists. Methods: ApoE −/− mice were divided into five groups: vehicle control (n = 5), DP1 receptor agonist (n = 5), DP1 receptor antagonist (n = 5), DP2 receptor agonist (n = 5), and DP2 receptor antagonist (n = 5), and the study was carried out for 10 weeks. Results: Despite being on high fat diet, mice receiving DP1 receptor agonist sustained a significant inhibition of weight gain throughout the study gaining only 11.4% body weight compared to the controls gaining 61% body weight. Interestingly, parallel to the body weight, the DP1 receptor agonist group showed a significant reduction in food intake throughout the study. Consistently, fasting leptin, insulin and bile acids levels were elevated in the DP1 receptor agonist group compared to controls. As expected, there was a significant reduction in fasting glucose level in DP1 receptor agonist group. At last, as a result of weight gain inhibition, DP1 receptor agonist also imparted cardiovascular benefits showing significant reduction in aortic wall thickness, intima, adventia and lumen size. Conclusion: Based on the obtained results, we believe DP1 receptor agonism inhibited diet induced weight gain possibly through controlling appetite which consequently imparted beneficial cardiometabolic effects. DP1 receptor agonism may represent a novel therapeutic target for the management of obesity.